The Efficacy of Unmanned Aerial Vehicles for Imagery and Remote Sensing - O'Donnell, Sean B; Smith, Connor J (DigitalCommons@Cedarville, 2015)
Over the past few years, unmanned aerial vehicles (UAV), also known as “drones,” have gained popularity and use in many activities. One such activity is using UAVs for imagery and remote sensing. UAVs provide two major benefits over other options such as aerial photography and ground surveys: they have low cost and high maneuverability, due to their small size and low energy usage. The cost of a UAV is variable, ranging from inexpensive with a poor camera (or no camera) around $30, to professional film grade from $1000-$4000. The models with camera capability worth using are usually near $400. Purchasing a UAV is possible online with little difficulty. Unmanned aerial vehicles have already proven useful in many different tasks and areas of geological research. UAV’s have been successfully used in such places as Galicia, Spain, to track boulder movement along beaches and provide high-resolution images of those boulders. They have also proven useful for landslide and rock fall monitoring and response. They can reach active or past events quickly, and provide a 3D assessment and images of the area. In Greenland, they have been used to monitor glacial calving events and processes. UAV’s have been used to make qualitative assessments and create high-quality magnetic intensity maps of the ground surface. In this use, they are just as capable as ground measurement and can overcome hazardous terrains. Researchers have also used UAV’s to capture high-resolution images of archaeological sites in Mexico. The possibilities for UAV use in geological research are extensive, and have been shown to be a reliable resource for imagery and remote sensing. Per their abilities, the use of UAVs can and should be expanded to other areas of geological research.